One-step synthesis of green emission carbon dots for selective and sensitive detection of nitrite ions and cellular imaging application. Issue 17 (9th March 2020) - Zan, Minghui; Li, Cong; Liao, Fei; Rao, Lang; Meng, Qian-Fang; Xie, Wei; Chen, Bei; Qie, Xingwang; Li, Li; Wang, Liang; Dong, Wen-Fei; Liu, Wei
Abstract : Schematic route of the carbon dots and their applications for the nitrite detection. Abstract : In recent years, carbon dot (CD)-based fluorescent sensors for selective ions or small biomolecules have drawn great attention. In this work, highly fluorescent CDs (QY = 21%) were prepared from 2, 3-diamino pyridine as the precursor through a facile solvothermal process. The CDs showed high stability and a green emission in aqueous, and the optimal emission wavelength of CDs is 508 nm under the excitation wavelength of 438 nm. Interestingly, a CDs-based nanoprobe was developed for a selective and sensitive fluorescence quenching response to NO2 − in water, and the quenching mechanism was investigated in the work. Besides, the recovery rates of NO2 − in the range of 98–103.5% were found to be acceptable, indicating that the proposed CDs could be act as potential candidates for determination of nitrite ions in real samples. Meanwhile, the nanoprobe was also successfully employed in a visualization biosensing platform for determination of NO2 − in living cells due to its eminent biocompatibility.